Protective Role of Coffee in Thioacetamide-induced Nephrotoxicity: A Study in Rats - Zaidi, Syeda Nuzhat Fatima; Mohiuddin, Amna; Gojayev, Anar; Jan, Afnan; Muhsinah, Abdullatif Bin; Khan, Ajmal (Current Pharmaceutical Biotechnology, 2025)
<span class=
Keywords: biochemical analysis